Fertirrigação em diferentes ciclos da cultura da bananeira - Silva, Maria Ivanísia de Sena da (2009)
The cultivation of bananas in FAPIJA-Federation of Producers Project Jaguaribe-Tableland, located in the northeastern state in Apodi Plateau, municipality of Limoeiro North - CE has evolved its quality standard and technological level of irrigated banana. This region stands out as the varieties of banana Pacovan, Silver, Willans, Apple, Nine and Grand Terrinha, respectively, in greater amounts of planted areas throughout the municipality. However, factor in the management need more detailed research to optimize the use of water and fertilizer through the irrigation management and fertilization techniques and useful information economically viable for banana growers in the region on irrigated cultivation of banana. This work was encouraged in order to evaluate the influence of different irrigation levels and potassium levels in vegetative development, production and detect chemical effects on leaf and fruit, under irrigation with a flow rate of 2.3 L h-1 and pressure of 2.0 bar during the fourth cycle of cultivation of banana cv. Pacovan Tableland. Also consisted in identifying the efficiency of irrigation, diagnose the irrigation and the application of potassium which obtained the highest yield in production. The experiment was conducted for determining evapotranspiration by the direct method in the lysimeter drainage at the farm FRUTACOR the period, 20/03/2008 to 14/04/2009, located within the Irrigation District Jaguaribe - Tableland (DIJA), located in City of North Limoeiro the State of Ceará, whose geographical coordinates are 5o06'38 "south latitude, 37o52'21" longitude west of Greenwich and altitude of 143 m. The experiment was done in randomized blocks arranged at random with plots and 03 (three) repetitions. The treatments were combinations of 05 (five) irrigation (50% = L1, L2 = 75% L3= 100%, L4 = 125% and L5 = 150%) of crop evapotranspiration, 04 potassium (K1 = 0%, K2 = 60%, K3 = 140% and K4 = 200% K indicated by the analysis of soil (kg ha-1). The reference evapotranspiration was determined by the Penman-Monteith-FAO program REF ET with data collected between March 20, 2008 to 06th 2009 From meteorological station installed in the area of the farm FRUTACOR. The fertigation was assessed weekly by a Venturi type injector with a flow rate of 5 L min-1 who used fertilizers in irrigation water. The values of Kc average initial phase, intermediate and final were 0.87, 1.01 and 0.88 respectively. The dependent variables evaluated for the 1, 2, 3 and 4 production cycles of the culture of banana cv. Pacovan Apodi for interaction irrigation and potassium levels, the number of fruit in the bunch, the number of hands, the weight of the bunch center, the fruit diameter and length of the fruit differed significantly (prob. <0.01) Interaction in Lamina versus potassium. The best treatments for the variables identified NFC and the NP L4K4 in the PPC L5K4 in the DF and CF L3K2 the L5K4. Aspects of quality of bananas: Total Soluble Solids and Concentration of potassium in the fruit were not positively affected by the interaction treatments versus Lamina Potassium for the mean values of four cycles